Implementation Of Village Funds In Implementation Of Development As An Effort To Improve Community Welfare In Kadiwono Village, Bulu District, Rembang Regency - Ahmad Ridwan; Widayati Widayati (Jurnal Daulat Hukum, 2020)
One of the most important things in Act No. 6 of 2014 on Villages is the existence of special rules contained therein which contain regarding village funds. Research will answer the problem formulation that is how the implementation of village funds in the form of implementation of development in the Kadiwono Village, Bulu District, Rembang Regency. The method of approach in this research uses the sociological juridical method with the research specifications descriptively analysis. The data used for this study are primary and secondary data taken from field observation, interviews, and literature study methods. Based on the research concluded in 2019, Kadiwono Village, Bulu District, Rembang Regency obtained Village Revenues totaling Rp 1,500,432,113 consisting of village funds, tax revenue-sharing, retribution sharing, village fund allocation, provincial financial assistance, district financial assistance, and the remaining 2018 budget (SILPA). In village expenditure, Kadiwono Village divides 4 areas in village expenditure through the allocation of village funds, namely (1) the field of village governance, (2) development, (3) community development, (4) and community empowerment.Keywords: Village Funds; Development; Public Welfare.